The Impact of IoT in Brick-and-Mortar Stores: How IoT and Customer Analytics are boosting customer engagement - Soares, Helena Margarida Ferrão (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence